CREDIT, BILLS, AND BOOKKEEPING IN A SIMPLE ECONOMY. - Baxter, W. T. (The Accounting Review, 1946)
From the point of view of the methods of exchange, there were three main stages of economic development the prehistorical or early medieval stage of natural economy, where goods were exchanged against other goods; the later medieval stage of cash money economy, where goods were bought for ready money; and the modern stage of credit economy, where commercial exchange was based on credit. If credit has played its important role for so long, then surely the history of book-keeping should supply further evidence on the point. Credit without written reckoning is almost impossible; the first and most fundamental reason for keeping accounts is to aid in remembering what one has trusted to their debtors. Early bookkeeping records fall into two groups, namely, the accounts themselves, and textbooks on accounting. A bad monetary system was still no unusual thing-even England did not put her coinage onto a moderately sound basis until 1696. But the plight of the New England colonies was exceptional. Nominally, their money consisted of pounds, shillings, and pence, each of these units being (in Massachusetts) worth about three-quarters of its British namesake.